Construção da via de interação do vírus Ebola com o hospedeiro e estimativa da origem dos genes e processos - Élisson Nogueira Lopes (2018)
Ebola virus (EBOV) is an enveloped, filamentous virus that contains a negativestranded RNA genome. EBOV belongs to the Filoviridae family, and causes a devastating disease, with a mortality rate of about 50-90%. The first symptoms developed by infected patients are fever, malaise and muscle pain and can be followed by bleeding and failure of organs and tissues. The initial targets of Ebola are macrophages and dendritic cells, but their ability to infect all types of cells, with the exception of lymphocytes. Ebola connects through the plasma membrane and, thereafter, a viral glycoprotein induces uptake by endocytosis. The process is dependent on the action of the proteins of the cell life. After absorption, as particles travel in compartments where a viral glycoprotein is cleaved and fused to the endosomal membrane, which results in the release of viral compartments without host cytoplasm. The study of the mechanism of infection of the EBOV and a collection of the hosted proteins was carried out, by participating directly or indirectly in the infection. This mining approach recruited 133 host proteins. With them, a complete interactive route was constructed to represent the Ebola infection cycle in hosts. An analysis was also made of the homologues of each human protein collected along the taxonomic tree to infer its clade/epoch the origin. The results of the analysis of evolutionary origin have allowed inferring that the virus can infect from Euleostomi, suggesting that animals such as fish and pets might be infected and retransmit the virus to other hosts, such as man. In addition, we analyzed two datasets, through KEGG enrichment, creating a profile of viral infection. Initially, processes involving cellular control and metabolism were enriched, followed by several other processes of immortalization and suppression of the immune system. In conclusion, an Ebola infection occurs with an interaction with old membrane and internal proteins, some still are younger. The construction of the pathway allows the creation of a systematic study of virus infection and what the possible therapeutic targets might be.